Intrusion detectionsystem - Low Kar Xin (School of Microelectronics, University Malaysia Perlis, 2015)
Security administration plays a vital role in network management task. The intrusion detection systems are primarily designed to protect the availability, confidentiality and integrity of critical network information systems. During recent years, number of intruders on networks has increased so there is a need of reliable network and this is the current hot topic among researchers. Intrusion detection is a technique to detect unauthorized access to the network. An intrusion detection system (IDS) monitors system and network to detect intruders that are trying to gather information on network for which they are not authorized. Snort is one of the IDS tool which can give alert to the authentication user or Network Administrator by giving alarm for misuse of network.